An overview of current trends in English language syllabus designes - YILMAZ VİRLAN, AYŞE (Duvar Yayınevi, 2022)
WHAT IS A SYLLABUS? A well-developed syllabus is an essential component of teaching no matter what you desire to accomplish in your classroom. To make the most of its benefits for the teaching-learning process, educators-and learners alike would benefit from a firm grasp of this issue. Considering the definition of a syllabus, it is well known traditionally that a syllabus is a detailed plan or program for a subject or course that may include the weekly topics that will be covered during the course as well as the materials that students are required to read, the evaluation of the course, and information about the assignments or projects that are expected to be completed. This means that a syllabus can serve as a roadmap for both students and teachers.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Social Sciences and Humanities; Education; Educational Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities